Effects of Ocean Acidification and Warming on Sperm Activity and Early Life Stages of the Mediterranean Mussel (Mytilus galloprovincialis) - Vihtakari, Mikko; Hendriks, Iris E.; Holding, Johnna; Renaud, Paul E.; Duarte, Carlos M.; Havenhand, Jon N. (Water, 2013)
Larval stages are among those most vulnerable to ocean acidification (OA). Projected atmospheric CO2 levels for the end of this century may lead to negative impacts on communities dominated by calcifying taxa with planktonic life stages. We exposed Mediterranean mussel (Mytilus galloprovincialis) sperm and early life stages to pHT levels of 8.0 (current pH) and 7.6 (2100 level) by manipulating pCO2 level (380 and 1000 ppm). Sperm activity was examined at ambient temperatures (16–17 °C) using individual males as replicates. We also assessed the effects of temperature (ambient and ≈20 °C) and pH on larval size, survival, respiration and calcification of late trochophore/early D-veliger stages using a cross-factorial design. Increased pCO2 had a negative effect on the percentage of motile sperm (mean response ratio R= 71%) and sperm swimming speed (R= 74%), possibly indicating reduced fertilization capacity of sperm in low concentrations. Increased temperature had a more prominent effect on larval stages than pCO2, reducing performance (RSize = 90% and RSurvival = 70%) and increasing energy demand (RRespiration = 429%). We observed no significant interactions between pCO2 and temperature. Our results suggest that increasing temperature might have a larger impact on very early larval stages of M. galloprovincialis than OA at levels predicted for the end of the century.